Analisis Penurunan Nilai Aset berdasarkan Sak Entitas Privat: Studi Literatur (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
This study examines asset impairment in private entities based on the Private Entity Financial Accounting Standards (SAK EP) to understand the mechanisms of identifying indicators, measurement methods, recognition procedures, and their impact on financial statements. Using a descriptive qualitative method, data were obtained from various sources such as the internet, financial reports, books, and journals, and then analyzed to provide a comprehensive depiction of impairment implementation. SAK EP requires entities to assess the presence of impairment indicators at the end of each reporting period and to calculate the recoverable amount as the higher of fair value less costs to sell or value in use. When the carrying amount of an asset exceeds its recoverable amount, the difference is recognized as an impairment loss. The findings indicate that asset impairment is influenced by internal factors such as declining asset performance, physical deterioration, and changes in estimated benefits, as well as external factors such as economic fluctuations, technological changes, and debtor default risk. Asset impairment affects the carrying amount of assets, net income, and financial ratios such as ROA and ROE, while enhancing the relevance, transparency, and reliability of financial information. This study emphasizes that the application of impairment in accordance with SAK EP plays a crucial role in ensuring that the financial statements of private entities reflect the actual economic conditions and provide reliable information for stakeholders.